Adaptive Immunity Regulation and Cerebral Ischemia - Qin, Xingping; Akter, Farhana; Qin, Lingxia; Cheng, Jing; Guo, Mei; Yao, Shun; Jian, Zhihong; Liu, Renzhong; Wu, Songlin (Frontiers in Immunology, 2020)
Stroke is a sudden interruption of the blood supply to the brain. It can be classified as hemorrhagic or ischemic and is a leading cause of death worldwide. It is well known that the immune system plays a major role in ischemic stroke and can be both advantageous and deleterious. The innate immune system and the adaptive system play distinct but synergistic roles following ischemia. The innate system can be activated by damage-associated molecular patterns, which are released from cells in the ischemic region. Damaged cells also release various other mediators that serve to increase inflammation and compromise the integrity of the blood brain barrier. Within 24 hours of an ischemic insult, the adaptive immune system is activated. This involves T-cell and B-cell mediated inflammatory and humoral effects. These cells also stimulate the release of various interleukins and cytokines, which can modulate the inflammatory response. The adaptive immune system has been shown to contribute to a state of immunodepression following an ischemic episode and this can increase risk of infections. However, this phenomenon is equally important to prevent autoimmunity of the body to brain antigens, which are released into the peripheral system as a result of blood brain barrier compromise. In this review we highlight the key components of the adaptive immune system that are activated following cerebral ischemia.